A controvérsia em torno dos escritos de Maimônides: o fortalecimento do discurso identitário judaico no Mishné Torá (1180-1204) - Rosado, Layli Oliveira (2013)
Maimonides was a twelfth-century rabbi, author of the Mishneh Torah, the Guide for the Perplexed and other writings, wich caused great controversy within the medieval Jewish community. The hostility on the writings of Maimonides became known as "maimonidean controversy", and had three important moments: in 1180; from 1230 to 1232; and from 1300 to 1306. This study is part of the first stage of this controversy, wich begins in 1180 and extends until the death of Maimonides, in 1204. This stage ocurred in the East and was a political and religious conflict. To support our analysis, we will use the Mishneh Torah, particularly the Book of Wisdom, and some of the author"s personal correspondences. We believe that Maimonides produced his Talmudic code in order to guide, or enlarge, the teachings of the Jewish doctrine in his time. A central focus of this paper is a discourse analysis of Maimonides in the Book of Wisdom, written under the cultural environment of the Muslim world, in order to understand it as an attempt to strengthening the medieval Jewish identity based on a rational systematization of Talmudic tradition.